Supporting Community-Managed Loan Funds - Murray, Jessica (2012)
Donors support many community-managed loan funds (CMLFs) often designed as components of larger projects. Unlike microfinance institutions (MFIs) with professional staff, CMLFs rely on group members themselves to manage the funds. CMLFs can be attractive alternatives for areas and populations that are too expensive for formal MFIs to reach. Savings-based models have experienced promising results, but funding CMLFs with external capital at the outset almost always leads to poor repayment rates and fund failure.